Synthesis and Characterization Analysis of Banana Peel Carbon Activated as Adsorption of Copper (Cu) - Mira Ayu Rahmawati; Abdul Ngalimus Salam; Wahyudi Nandana Munte; Nidya Chitraningrum; Lita Rahmasari (School of Postgraduate Studies, Diponegoro Univer, 2025)
Activated carbon is a porous material widely used in various industrial and environmental applications, especially as an adsorbent in liquid waste treatment and gas purification. Banana peel, an abundant and renewable carbon source, is an environmentally friendly and sustainable raw material for activated carbon. However, optimization of the activation process is essential to improve the characteristics and adsorption performance of activated carbon. This study aims to evaluate the effect of KOH activation on the synthesis and characterization of banana peel-based activated carbon. Carbonization and chemical activation processes were carried out, then morphology and chemical structure characterization were performed using Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray (EDX), and Fourier Transform Infrared Spectroscopy (FTIR). The analysis showed that the activated carbon obtained has a well-developed pore structure with a porosity level of 74.80% and contains O-H, C-H, C=O, and C-Cl functional groups, which play a role in metal ion interactions. The hydrophilic nature of the activated carbon was studied through contact angle analysis, while the adsorption capacity towards copper ions (Cu) was determined using an Atomic Absorption Spectrophotometer (AAS). The results showed that the highest adsorption efficiency of 99.99% was achieved on activated carbon with 20% concentration and 15 minutes contact time. With good pore characteristics and high adsorption efficiency, banana peel-based activated carbon has the potential to be an efficient and sustainable adsorbent in heavy metal waste treatment applications. This research provides further insight into the utilization of biomass waste to produce functional materials of high-added value.